Rancang Bangun Sistem Automatic Keamanan Jarak Pada Truk Trailer Menggunakan Sensor Jarak Berbasis Internet Of Things - Abdillah, Aditya Ryan; Siregar, M. Fadlan; Satria, Habib; Mungkin, Moranain (Jurnal Ilmiah Teknik Informatika & Elektro (JITEK), 2024)
One of the causes of accidents that occur on the road is a condition where there is an error in the human factor which lacks focus in observing the circumstances around the vehicle being driven. For drivers of large vehicles such as trucks, they have areas where sight cannot reach or what is commonly called a blind spot, which is due to the large dimensions so that the viewing angle is limited. This situation results in the risk of large vehicles hitting other drivers or other objects that are in the blind spot area. This study aims to design a tool to assist drivers in providing information and warnings if there is an object in the blind spot area. This tool uses an ultrasonic sensor as an object detector, as well as an information system that is sent via wifi and displayed on the Blynk application to determine the distance and location of objects. Testing is carried out by applying it directly to the vehicle to determine the performance of the tool on the vehicle